The mid point of two points (x1, y1) and (x2, y2) is [(x1 + x2)/2, (y1 + y2)/2)]

The points we have are (-1 , 2) and (3 , -6)

The mid point of these is [(3 - 1)/2 , (2 - 6)/2]

=> (1 , -2)

**The mid point is (1 , -2)**

The midpoint between any two points A(xa, ya) and B(xb, yb) has the x coordinate that is the average of the x-coordinates of the two points and the y coordinate that is the average of the y coordinates.

Here, the points are A(-1, 2) and B(3, -6).

The average of the x coordinates is (-1 + 3)/2 = 1 and the average of the y coordinates is (2 - 6)/2 = -2

The coordinates of the mid point between (-1, 2) and (3, -6) is (1, -2)

We'll apply the midpoint formula:

M = (xM ; yM)

xM = (x1 + x2)/2

yM = (y1+y2)/2

x1,x2,y1,y2 are the coordinates of the given points. Since the coordinates are added, it doesn't matter which point is the first one, whose coordinates are x1 and y1, and which point is the second one.

We'll identify x1 = -1, x2 = 3, y1 = 2 and y2 = -6

Now, we'll calculate the coordinates of the midpoint:

xM = (-1+3)/2

xM = 1

yM = (2 - 6)/2

yM = -2

**The coordinates of the midpoint M are: M(1 ; -2).**